898. HELICHRYSUM 'SUN BURST': Compositae. (4th January 2019) - Strange, Kit; Hind, Nicholas
Summary: A new cultivar, Helichrysum 'Sun Burst' (Compositae: Inuleae: Gnaphaliinae), is introduced, described, and illustrated, based on material derived from a cross between a Turkish collection of H. orientale and H. arwae from the Yemen Arab Republic, growing in the Melon Yard, Alpine Nursery at the Royal Botanic Gardens, Kew. Cultivation and propagation notes are provided. Observations on the diurnal rhythm of the capitula are made, as well as the overlapping flowering time of the parent species in the wild, but possessing a significantly different geographical distribution.